Pembentukan Pendidikan Karakter Pelatihan Menulis Pantun Bagi Mahasiswa PGSD UPI Kampus Purwakarta - Mamad Kasmad; Acep Ruswan; Sopyan Iskandar; Gia Nikawanti; Gina Novianti (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Preserving Indonesian culture is our collective duty, in its realization as prospective teachers for UPI students at the Purwakarta campus, they are equipped with an understanding of character education through Pantun problems to convey moral messages in learning, especially strengthening, forming, and developing the potential of students in thinking and behaving well, filtering and choosing the nation's own culture, so that it can filter out the culture of other nations that are not by the values of the character and culture of the nation itself. To make those idea happen, the objectives of this community service were the following questions: (1) do UPI Purwakarta Campus students master Pantun? (2) do students of PGSD UPI Campus Purwakarta master the type of Pantun? and (3) are PGSD UPI Purwakarta students able to bring up character values in making Pantun? The participants of this training consisted of 50 students from various classes, the focus of this service is through Pantun training which was carried out online and the outputs in this community service training were articles publications in the field of community service and Pantun training videos so that it is hoped that UPI PGSD Purwakarta students as teacher candidates not only skilled in teaching but equipped with character education. The learning process either before or after learning can interact directly with choosing words adapted to different learning themes.